2019
DOI: 10.1016/j.juro.2018.08.083
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Robotic Unilateral Extravesical Ureteral Reimplantation in the Pediatric Population: Short-Term Assessment of Safety

Abstract: Robotic unilateral extravesical ureteral reimplantation is safe as an outpatient procedure in the pediatric population. Further evaluation is warranted to assess its short- and long-term outcomes on a larger scale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Our surgical technique for the various procedures has been previously published. 5,6 The Intuitive SurgicalÒ da Vinci S and Xi surgical systems were utilized during the study period. One camera trocar in the umbilicus and 2 instrument trocars were utilized without any bedside assistant ports.…”
Section: Methodsmentioning
confidence: 99%
“…Our surgical technique for the various procedures has been previously published. 5,6 The Intuitive SurgicalÒ da Vinci S and Xi surgical systems were utilized during the study period. One camera trocar in the umbilicus and 2 instrument trocars were utilized without any bedside assistant ports.…”
Section: Methodsmentioning
confidence: 99%
“…Neheman et al (page 615) from Israel and Cincinnati, Ohio report on the safety of performing robotic extravesical ureteral reimplantation. 2 Among their small group of patients undergoing outpatient robotic ureteral reimplantation none had a Clavien-Dindo grade III or higher complication. The authors have shown that it is possible to create and work with the robot in the confined space of the pelvis and manipulate the ureter, although it remains to be established whether this is the best sequence of maneuvers.…”
Section: Outpatient Robotic Ureteral Reimplantationmentioning
confidence: 96%
“…published a retrospective study of 27 pediatric patients who underwent RALUR-EV as an outpatient procedure, which reported promising results. [ 41 ] While additional studies on RALUR as an outpatient procedure are needed to assess its long-term outcomes with larger sample sizes, this innovative care pathway could eventually transform the current landscape of this procedure. With the possibility of performing RALUR as an outpatient procedure, we can potentially cater to the care of children by providing the potential option for them to recover in a comfortable and familiar environment.…”
Section: Ureteral Reimplantationmentioning
confidence: 99%